Cell cycle regulation of CDK2 activity by phosphorylation of Thr160 and Tyr15. - Gu, Y (1992)
We have examined the role of phosphorylation in the regulation of human cyclin-dependent kinase-2 (CDK2), a protein closely related to the cell cycle regulatory kinase CDC2. We find that CDK2 from HeLa cells contains three major tryptic phosphopeptides. Analysis of site-directed mutant proteins, expressed by transient transfection of COS cells, demonstrates that the two major phosphorylation sites are Tyr15 (Y15) and Thr160 (T160). Additional phosphorylation probably occurs on Thr14 (T14). Replacement of T160 with alanine abolishes the kinase activity of CDK2, indicating that phosphorylation at this site (as in CDC2) is required for kinase activity. Mutation of Y15 and T14 stimulates kinase activity, demonstrating that phosphorylation at these sites (as in CDC2) is inhibitory. Similarly, CDK2 is activated in vitro by dephosphorylation of Y15 and T14 by the phosphatase CDC25. Analysis of HeLa cells synchronized at various cell cycle stages indicates that CDK2 phosphorylation on T160 increases during S phase and G2, when CDK2 is most active. Phosphorylation on the inhibitory sites T14 and Y15 is also maximal during S phase and G2. Thus, the activity of a subpopulation of CDK2 molecules is inhibited at a time in the cell cycle when overall CDK2 activity is increased.